A Fresh Approach to Social Work Placements. Issue 1 (1st January 2023) - Repesa, Alma; Rawlins, Alison; Ludwell, Sara-Eden; Maslen, Liz
Abstract : Social Work Teaching Partnerships were initiated by the UK government in 2015. The purpose was to improve the quality of social work education and training. In the East Midlands, four Local Authorities (Derbyshire, Derby City, Nottinghamshire and Nottingham City) joined with other local organisations to form the "D2N2" Social Work Teaching Partnership (the D2N2 acronym representing the two Derbyshire and two Nottinghamshire local authorities). The Partnership was formally recognised as a Teaching Partnership in 2016. As part of our commitment to improving social work education and training, we identified a need to develop our practice education (field education) further, by developing a revised and improved placement quality assurance system that replaced the Quality Assurance in Practice Learning (QAPL) system, which was not felt to be fit for purpose. This work formed part of a wider Placement Learning System (PLS) and Practice Development Programme (PDP), which were developed in conjunction with the Universities and employer organisations. The PLS enhanced the voice of the student whilst at the same time allowing us to gather a significant amount of data about the quality of placements; and the PDP allowed us to develop our practice educator cohort. This article explores these developments.